Tinjauan Atas Pioderma - Inosensia Diajeng Kusumo; Kenny (PT Kalbe Farma Tbk., 2022)
Pioderma adalah infeksi kulit piogenik yang sering disebabkan oleh Staphylococcus aureus dan Streptococcus grup A. Diagnosis umumnya ditegakkan melalui tampilan klinis. Tata laksana meliputi antibiotik disertai insisi dan drainase bila perlu. Terapi antibiotik secara empiris disesuaikan dengan derajat keparahan penyakit. Pyoderma is pyogenic skin infection and commonly caused by Staphylococcus aureus and group A Streptococcus. Diagnosis can be established by its clinical features. Treatment consists of antimicrobial therapy accompanied with incision and drainage as indicated. Antimicrobial therapy is given empirically and adjusted depending on severity of the disease.